Modelling and development of asphalt pavement thermoelectric energy harvesting system using subterranean cooling / Khairun Nisa Khamil - Khairun Nisa , Khamil (2021)
In this study, waste heat from Malaysia's road pavement was utilized to develop a system using thermoelectric energy harvesting (TEH) with a subterranean cooling method. As there are various of thermoelectric module (TEM) on the market, this makes it challenging to select the right TEM for a particular application and most manufacturer does not share all the required information. Hence, the fundamental equations were modelled using MATLAB/SIMULINK, and the characterization of a suitable thermoelectric module (TEM) was investigated using different placement configurations for a rapid output performance. Meanwhile, a three-dimensional finite element analysis (FEA) model is developed using a COMSOL Multiphysics as a replacement model to assess various problems affecting the system properties, predict the outcome and optimize without engaging the actual experiment. The system structure consists of the heat receiver down to the system's cooling element to produce high-temperature differences for the selected TEM. Sustaining the maximum power point (MPP) required a particular load resistor and current from TEM, and the MPP current depends on the temperature difference to generate high power. Therefore, a power management circuit (PMC) with a boost converter capability and an MPP tracker applicable to the ambient temperature of the asphalt road surface was determined in this study. Based on the results, the modelling using MATLAB/SIMULINK has expedited estimating the electrical performances of specific parameters needed using any on-the-shelf module. Using a smaller TEM size and the configuration placement between the cascading module on the module caused the heat to transfer much more efficiently and significantly influenced the output generated. The internal resistance obtained from the modelling was used for load matching to attain the maximum power transfer from a source to a load used in the field experiment. Whereas the FEA's simulation results were validated with the experimental result, given a margin of error of less than 5%, the results give a 95% confidence level. The temperature difference and output generated from the system are influenced by the conduction shape factor and the radiation heat transfer on the TEHs structure. The novel TEHs structure consists of a heat receiver with a dimension of 10 cm by 20 cm and two cylindrical rods anchored between an aluminium plate welded under a 6.5 cm by 20 cm of bottom plates as a cooling element gives a maximum of temperature difference 23.2 °C with 1.02V of the output voltage. Based on the feasibility studies with an application, the TEHs have effectively fully charged 5 Farad supercapacitors within 3 hours to use automatic street LED lights, substantiating TEHs design's significance. The present study represents a new perspective for self-sustainable TEHs design integrated with the high cooling performances of the H-shape element in subterranean cooling.